Answer:
sorry sir i dont really know sir
Answer:
given
n=9
a=1
d=3-1=2
Step-by-step explanation:
now , by formula,
sn = n/2(2a+(n-1)d)
= 9/2(2×1+(9-1)×2)
=9/2×18
=81
Answer:
Let the present age of the man be x years.
Age of the man 15 years ago =(x−15) years and
Age of the man 15 years later =(x+15) years
According to the given condition, we have
(x+15)=2(x−15)
⇒x+15=2x−30
⇒x−2x=−30−15
⇒−x=−45 or x=45 years
Hence, the present age of the man is 45 years.
Step-by-step explanation:
Hope it helps you..
Your welcome in advance..
(◍•ᴗ•◍)
Answer:
6x - 6
Step-by-step explanation:
<em>The only step necessary here is to simplify. We can subtract 18 from 12 since they are like terms. </em>
6x - 6.
<em>That's it! That's your final answer. </em>